Respuesta :
use FOIL method first to get rid of ()
x^2 - 4x + 4x -16 = 9
x^2 - 16 = 9
move the 16 over by addition
x^2 = 25
Then take the square root and get
x = 5
x^2 - 4x + 4x -16 = 9
x^2 - 16 = 9
move the 16 over by addition
x^2 = 25
Then take the square root and get
x = 5
perform indicated operations on left side
x*x+4x+4x+4*4=9
x^2+4x+4x+16=9 combine like terms on left side
x^2+8x+16=9 subtract 9 from both sides
x^2+8x+7=0 factor
x^2+x+7x+7=0
x(x+1)+7(x+1)=0
(x+7)(x+1)=0
x=-1, -7
x*x+4x+4x+4*4=9
x^2+4x+4x+16=9 combine like terms on left side
x^2+8x+16=9 subtract 9 from both sides
x^2+8x+7=0 factor
x^2+x+7x+7=0
x(x+1)+7(x+1)=0
(x+7)(x+1)=0
x=-1, -7